2009
DOI: 10.1002/mnfr.200800480
|View full text |Cite
|
Sign up to set email alerts
|

Impact of arsenic on nucleotide excision repair: XPC function, protein level, and gene expression

Abstract: The ubiquitous occurrence of the human carcinogen arsenic results in multiple exposure possibilities to humans. The human diet, especially drinking water, is the primary source of inorganic arsenic intake in the general population. The ingested arsenic is metabolized to methylated derivatives; some of these metabolites are today considered to be more toxic than the inorganic species. Various modes of action have been proposed to contribute to arsenic carcinogenicity; inhibition of nucleotide excision repair (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 57 publications
2
36
1
Order By: Relevance
“…DMA V , the only methylated metabolite of inorganic arsenic that has been studied in this respect did not change the expression of DNA repair genes, including XPB, of bladder transitional epithelium in F344 rats [52]. Most recently, Nollen et al [53] found that a 24-h treatment with arsenite or MMA III strongly decreased XPC at both the mRNA and protein levels in normal human skin fibroblasts immortalized by telomerase transfection (VH10hTert). The reduced level of XPC expression led to a diminished localization of XPC to UV-damaged spots in the nucleus.…”
Section: Possible Mechanisms Of Ner Inhibition By Arsenic 41 Arsenicmentioning
confidence: 92%
“…DMA V , the only methylated metabolite of inorganic arsenic that has been studied in this respect did not change the expression of DNA repair genes, including XPB, of bladder transitional epithelium in F344 rats [52]. Most recently, Nollen et al [53] found that a 24-h treatment with arsenite or MMA III strongly decreased XPC at both the mRNA and protein levels in normal human skin fibroblasts immortalized by telomerase transfection (VH10hTert). The reduced level of XPC expression led to a diminished localization of XPC to UV-damaged spots in the nucleus.…”
Section: Possible Mechanisms Of Ner Inhibition By Arsenic 41 Arsenicmentioning
confidence: 92%
“…Among the indirect genotoxic effects are also changes in the expression of genes of specific DNA repair proteins. Methylated arsenic compounds thus cause a reduction in xeroderma pigmentosum protein C (XPC) expression, which is a major damage recognition protein in nucleotide excision repair (Nollen et al 2008). …”
mentioning
confidence: 99%
“…XPC is actively involved in the recognition and initiation of cisplatin-DNA damage repair in GGR (Earley and Turchi, 2010;Neher, et aL, 2010). Arsenic has been shown to inhibit NER by inhibiting XPC expression (Nollen, et aL, 2009). In the current study, I observed that P53 and XPC were induced by cisplatin.…”
Section: Platinum and Arsenic Biodistribution In Somatic Tissuesmentioning
confidence: 99%
“…Mechanisms of arsenic induced cytotoxicity include: inhibition of nucleotide excision repair (Hartwig, et aL, 1997;Hartwig, et aL, 2003;Nollen, et aL, 2009;, causation of oxidative stress (Shi, et aL, 2004b;Shi, et aI., 2004a), induction of mitotic catastrophe (Taylor, et aL, 2008;McNeely, et aL, 2008a) and induction of apoptotic cell death (HU, et aL, 2005;Ramos, et aL, 2005). Resistance to arsenic is associated with enhanced metallothionein binding, detoxification by glutathione conjugation and efflux by multi-drug resistance proteins (Leslie, et aL, 2004), similar to cisplatin and its analogues (Cole, et aL, 1994;Byun, et aL, 2005;Surowiak, et aL, 2005).…”
Section: General Introductionmentioning
confidence: 99%
See 1 more Smart Citation